2000
DOI: 10.2139/ssrn.1524289
|View full text |Cite
|
Sign up to set email alerts
|

R&D and Technology Spillovers Via FDI: Innovation and Absorptive Capacity

Abstract: Two faces of R&D (innovation and learning) and technology spillovers from FDI (foreign direct investment) on a Þrm's productivity growth are examined in this paper. Using Þrm-level panel data on Czech manufacturing Þrms between 1995 and 1998, I Þnd that: (i) the learning effect of R&D is far more important than the innovative effect in explaining the productivity growth of a Þrm, (ii) there is no evidence of technology spillovers to local Þrms from having a foreign joint venture partner, (iii) positive spillov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
165
4
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(194 citation statements)
references
References 24 publications
14
165
4
11
Order By: Relevance
“…É, contudo, difícil, como salienta Kinoshita (2001), distinguir na prática os diferentes canais, dado que os mecanismos geradores de externalidades do IDE são complexos e interdependentes.…”
Section: Os Canais De Geração De Externalidadesunclassified
See 1 more Smart Citation
“…É, contudo, difícil, como salienta Kinoshita (2001), distinguir na prática os diferentes canais, dado que os mecanismos geradores de externalidades do IDE são complexos e interdependentes.…”
Section: Os Canais De Geração De Externalidadesunclassified
“…Por outro lado, tem sido defendida a existência de uma dimensão regional/local na ocorrência de externalidades, de tal forma que seriam as empresas nacionais geograficamente mais próximas das EM as que se beneficiariam de modo mais significativo. A análise empírica desenvolvida em relação a estes dois fatores confere um sólido suporte ao primeiro argumento (Kinoshita, 2001;Schoors e van der Tol, 2002;Kanturia, 2002;Keller e Yeaple, 2003;Girma, 2003;Karpaty e Lundberg, 2004), mas é mais ambígua no que se refere ao segundo fator (Sjöholm, 1999b;Aitken e Harrison,1999;Girma e Wakelin, 2000;Girma, 2003;Yudaeva et al, 2003;Torlak, 2004).…”
Section: Que Perspectivas Para a Investigação Sobre Externalidades Dounclassified
“…Finally, studies that proxy technology by the level of R&D consistently find positive horizontal spillovers in the R&D sector (see e.g. Kinoshita, 2000, using data from the Czech Republic). Sabirianova, Svejnar and Terrell (2005) use 1992-2000 firm-level data on the population of industrial firms in the Czech Republic and Russia and find that the productivity gap between domestic and foreign firms is increasing in industries with a greater foreign presence.…”
mentioning
confidence: 92%
“…In his study of intra-industry spillovers from FDI in Uruguayan manufacturing plants, Kokko et al (1996) found a positive and statistically significant spillover effect only in indigenous plants with moderate technology gaps relative to foreign firms, pointing to the existence of firm-specific differences in the ability to absorb spillovers from foreign firms. Cohen & Levinthal (1989) and Kinoshita (2000) suggested that the contradictory empirical findings might imply that the incidence of productivity spillovers requires the indigenous firms to possess the ability to absorb advanced technology from foreign firms.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%